The encyclopedia of Christianity - Fahlbusch, Erwin; Bromiley, G. W. (Geoffrey William) (Grand Rapids, Mich. : Wm. B. Eerdmans ; Leiden, Netherlands : Brill, 1952)
"The Encyclopedia of Christianity is the first of a five-volume English translation of the third revised edition of Evangelisches Kirchenlexikon. Its German articles have been tailored to suit an English readership, and articles of special interest to English readers have been added. The encyclopedia describes Christianity through its 2000-year history within a global context, taking into account other religions and philosophies. A special feature is the statistical information dispersed throughout the articles on the continents and over 170 countries. Social and cultural coverage is given to such issues as racism, genocide, and armaments, while historical content shows the development of biblical and apostolic traditions. This comprehensive work, while scholarly, is intended for a wide audience and will set the standard for reference works on Christianity."--"Outstanding reference sources 2000", American Libraries, May 2000. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references and index.
Keywords: Christianity -- Encyclopedias